Influence of fractal photostimulation on electroretinogram in patients with dry age-related macular degeneration - N. V. Neroeva; M. V. Zueva; V. I. Kotelin; I. V. Tsapenko; L. A. Katargina; Yu. S. Timofeev (Российский офтальмологический журнал)
In visual rehabilitation, the search for methods based on the activation of neuroplasticity is relevant, which includes the technology of fractal photostimulation (FP). Previously, a positive effect of FP courses on the function and structure of the retina was demonstrated on animals with a model of retinal pigment epithelium atrophy. On the other hand, the advantages of virtual reality (VR) technologies for visual training in a game format that increases patient compliance are known. The purpose of this work was to evaluate the effect of a FP course in VR on objective electroretinography parameters in patients with dry age-related macular degeneration (AMD). Material and methods. In 20 patients with dry AMD, intermediate and late stages, an ERG complex was recorded according to ISCEV standards before and in dynamics after a 2-week FP course. Results. A positive effect of FP on the activity of photoreceptors, as well as (to a slightly lesser extent) bipolar cells of the scotopic and photopic systems with a greater response to phototherapy of cone-related neurons were shown. The activating effect of FP on the outer retina was greatest in the early stages after the course of visual training. The positive effect of FP on the activity of retinal ganglion cells increased after the completion of the course for at least 1 month. The dynamics of multifocal ERG indicates a generalized activating effect of FP on the macula. Conclusion. The results of the study substantiate the prospects of fractal phototherapy as a method of visual rehabilitation that improves the functionality of the retinal neural network. It can also serve as a factor slowing down the progression of the degenerative process in the outer and inner retina.